Dirt Road and Trees - Unknown:::Creator::::::::::::
Number 2 of 10 Steinbeck locations: a deserted dirt road, arched over by oak trees. Others in this series are numbers 0-064, 0-810, 0-811, 0-812, 0-813, 0-814, 0-815, 0-816, 0-817